Asian elephant self-medication as a source of ethnoveterinary knowledge among Karen mahouts in northern Thailand - Alexander M. Greene (2020)
© 2020 Elsevier B.V. Ethnopharmacological relevance: Ethnoveterinary medicine is often assumed to be a subset of human medicinal knowledge. Here we investigate the possibility that some ethnoveterinary medicine rather originates from observations of animal self-medication. We document and analyze the ethnoveterinary medicine used by Karen mahouts for elephant care and attempt to determine whether this knowledge originated from humans or elephants. Materials and methods: Elephant camp owners and mahouts in four communities in northern Thailand were interviewed about their knowledge and use of plants for ethnoveterinary elephant care. For each ethnoveterinary plant, data were collected on Karen human medicinal uses and whether elephants independently consume them. Based on overlaps between ethnoveterinary use, human medicinal use and elephant dietary use, plants were classified into three categories: those that originated from Karen human medicine, those that originated from Asian elephant self-medication, and those which were present in both human and elephant knowledge traditions. Results: The use of 34 plants (32 identified at least to genus) and two additional non-plant remedies (salt and human urine) were reported to be used in ethnoveterinary elephant medicine. A total of 44 treatments in 11 use categories were recorded: tonic, wounds, compress, eye problems, indigestion, broken bones, galactagogue, snakebite, fatigue, skin and musth regulation. Of the ethnoveterinary plants, 55% had the same use in human medicine, 43% had different uses and 2% had no use. Elephants consume 84% of the ethnoveterinary plants as part of their natural diet. Discussion: Analysis indicates that 32% of plant uses likely originated from Karen human medicine, 60% of plant uses likely existed independently in both human and elephant knowledge systems, and 8% of plant uses likely originated from elephant self-medicating behavior. The tonic use category shows the strongest evidence of influence from observations of elephant self-medication. The use of tonic medicines appears to be increasing as a way to mitigate the unnaturally limited diet of elephants in tourist camps. Conclusion: Ethnoveterinary medicine for elephant care is influenced by both human medicinal knowledge and elephant knowledge of plants for self-medication. The ethnoveterinary knowledge domain appears to be the result of an interactive process linked to convergent evolution or co-evolution between humans and Asian elephants.